2012
DOI: 10.1007/s10103-012-1149-5
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokine levels in saliva in patients with burning mouth syndrome before and after treatment with low-level laser therapy

Abstract: The aim of this study was to determine the levels of proinflammatory tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) cytokines in whole unstimulated saliva in subjects with burning mouth syndrome (BMS) before and after treatment with low-level laser therapy (LLLT). BMS is characterized by a continuous, painful burning sensation in a clinically normal-appearing oral mucosa. A sample consisting of 40 consecutive subjects was selected on a voluntary basis from the pool of patients who presented for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 18 publications
6
86
3
Order By: Relevance
“…15 In another experimental model, a 685 nm LLLT with 3.0 J/cm 2 also significantly reduced the expression of TNF-a and IL-6 in the saliva of subjects with burning mouth syndrome. 19 These previous studies, which involved the analysis of several inflammatory mediators, including TNF-a, IL-1b and IL-6, demonstrated the effectiveness of LLLT in treating the inflammatory process, and also indicated the property of laser light on modulation of these proinflammatory mediators, especially for the LLLT with LF in attenuating the general inflammatory process and the expression of TNF-a. This can probably be explained by different applications of various wavelengths and fluences in these experimental trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In another experimental model, a 685 nm LLLT with 3.0 J/cm 2 also significantly reduced the expression of TNF-a and IL-6 in the saliva of subjects with burning mouth syndrome. 19 These previous studies, which involved the analysis of several inflammatory mediators, including TNF-a, IL-1b and IL-6, demonstrated the effectiveness of LLLT in treating the inflammatory process, and also indicated the property of laser light on modulation of these proinflammatory mediators, especially for the LLLT with LF in attenuating the general inflammatory process and the expression of TNF-a. This can probably be explained by different applications of various wavelengths and fluences in these experimental trials.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with several studies that showed the modulation of TNF-a by LLLT with LF. 17,19 Currently, there is a growing consensus that various proinflammatory cytokines produced by stimulated synovial macrophages are partly responsible for triggering the morphological changes that are found in joint cartilage caused by MMPs. 25 Therefore, MMPs and cytokines (IL-1, IL-6, and TNF-a) are responsible for the inflammatory signals that occur in the breakdown of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Romeo et al 68 % of BMS patients reported significant relief after LLLT 32 . Statistically significant reduction in the salivary levels of proinflammatory cytokines TNF-α and IL-6 was observed after the application of LLLT in BMS patients 27 . In the treatment of TN, LLLT has proven effective in several studies [33][34][35] .…”
Section: Discussionmentioning
confidence: 88%
“…Tongue biopsies in BMS patients showed a significant reduction of epithelial nerve fibres versus 25,26 . The treatment of neuropathic pain conditions often involves a variety of medicines with many side effects and, as the treatment continues, the need for extra dosage increase 27,28 . Medicinal management often includes antidepressants but, as studied by Tammialia-Salonen et al antidepressants did not effectively relieve BMS associated symptoms 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Burning Mouth Syndrome (BMS) is defined as a feeling of pain and burning in the normal oral mucosa, especially on the tongue, which affects other mucosal surfaces, including the lips, buccal mucosa and the floor of the mouth (1).…”
Section: Introductionmentioning
confidence: 99%